Cyberporn and Criminal Responsibility - Hendra Sitio (Universitas Negeri Semarang, 2019)
This research is based on cyberporn which is increasingly prevalent in Indonesian crime with internet technology as a medium of crime in cyberspace. Many problems are the basis of the author's research. The results of this study indicate that this criminal law policy has weaknesses and shortcomings, such as jurisdiction issues, the absence of specific arrangements regarding cyberporn, cyberporn issues in positive criminal law are regulated as crimes that violate decency There are weaknesses and deficiencies in current criminal law policy shows the need for a criminal law formulation policy in the effort to combat cyberporn. Future criminal law formulation policies relating to dealing with cyberporn. by paying attention to the characteristics of cyberporn as an information technology-based crime (occurring in cyberspace) and is transnational in nature, both at the stage of criminalization, determination of jurisdictional aspects, subject of criminal acts, criminal formulation system, criminal liability formulation system, criminal sanction formulation system and formulation of guidelines for criminal sanctions. criminal prosecution. Thus, it is very much needed special regulation of the problem of cyberporn in the formulation of criminal law that will come in order to maximize efforts to prevent and prevent cyberporn in Indonesia. The conclusion of this research is that the formulation of criminal acts does not explicitly or specifically regulate cyberporn, the system of formulating criminal sanctions that is not appropriate, the regulation and rules of criminal punishment are not regulated, and there is no harmonization of the substance of criminal acts and criminal formulation policies, both at national, regional and international levels.